Finite Element Analysis of Seepage and Exit Gradient through a Homogeneous Earth Dam without Cut-Off Walls and Filter Drain by using Geo-Slope (SEEP/W) Software - Arshad, Imran; Babar, Muhammed Muneer (International Journal of Alternative Fuels and Energy, 2020)
All dams experience seepage to some degree. While the dam experiencing seepage may appear in sound condition there may be damage occurring to the internal structure of the dam. A key factor to stability is the location of the phreatic line or the fully saturated zone of the soils within the embankment. In safe dams, this level is well confined below the surface. Since soils that are fully saturated are not as strong a higher phreatic line can reduce the ability of the embankment to resist sliding. This is often noted by seepage exiting on the downstream face of the dam. Weak or poorly compacted soils can increase both seepage and the phreatic level as well as weaken the embankment contributing to a sliding failure of the dam. In this study, a homogeneous section of an earthen dam (Hub dam) with and without cut-off wall and filter drain was analyzed by using FEM based software SEEP/W. The FEM model was run to compute the behavior of the dam in terms of seepage flux and exit gradient for three different scenarios i.e. maximum (346 ft), minimum (270 ft), and normal pool level (339 ft) respectively. The simulated results for case (i) with cut-off wall and filter drain showed that the dam is safe against piping, at its original design with overall minimum seepage flux of (2.513 x 10-4 ft3/sec/ft) and exit gradient (0.351) at downstream toe respectively. However, for case (ii) without cut-off wall and filter drain, the dam showed abnormal behavior as overall extremely high exit gradient (3.112) along with the maximum overall seepage flux of order 165.81 x 10-4 ft3/sec/ft respectively. The comparison showed that seepage flux (90.176% – 97.611%) and exit gradient (78.880% – 83.386%) through the dam and its foundation was found more when there are no cut-off wall and filter drain. Which is the result of continuous movement of the water within the dam especially in the foundation, as there is no any barrier installed to control internal pore water pressure, due to which the water seeping from the upstream and foundation finds its way moving towards the downstream and cuts the toe to make its way out respectively.